Misalignment Between Supply and Demand of Quality Content in Peer Production Communities - Warncke-Wang, Morten; Ranjan, Vivek; Terveen, Loren; Hecht, Brent (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
In peer production communities, individual community members typically decide for themselves where to make contributions, often driven by factors such as “fun” or a belief that “information should be free”. However, the extent to which this bottom-up, interest-driven content production paradigm meets the needs of consumers of this content is unclear. In this paper, we introduce an analytical framework for studying the relationship between content production and consumption in peer production communities. Applying our framework to four large Wikipedia language editions, we find extensive misalignment between production and consumption in all of them. We also show that this misalignment has an enormous effect on Wikipedias readers. For example, over 1.5 billion monthly pageviews in the English Wikipedia go to articles that would be of much higher quality if editors optimally distributed their work to meet reader demand. Examining misalignment in more detail, we observe that there is an excess of high-quality content about certain specific topics, and that the majority of articles with insufficient quality are in a stable state (i.e. not breaking news). Finally, we discuss technolo- gies and community practises that can help reduce the misalignment between the supply of and demand for high-quality content in peer production communities.